Some Identities of Fully Degenerate r-Dowling Polynomials Arising from λ-Umbral Calculus - Xiaoxue Li; Siqi Dong; Yuankui Ma (Mathematics, 2025)
This paper introduces fully Dowling polynomials of the first and second kinds, which are degenerate versions of the ordinary Dowling polynomials. Then, several important identities for these degenerate polynomials are derived. The relationship between fully degenerate Dowling polynomials and fully degenerate Bell polynomials, degenerate Bernoulli polynomials, degenerate Euler polynomials, and so on is obtained using umbral calculus.